1985
DOI: 10.1007/bf00964632
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline ribonuclease activity is increased in rat sympathetic ganglia after nerve injury

Abstract: Ribonuclease activity at pH 7.1 ("alkaline" ribonuclease) was determined in homogenates of rat superior cervical ganglion up to 5 days after postganglionic nerve injury under optimal conditions of assay. Measurements were performed in the presence and absence of the sulfhydryl blocking agent, N-ethylmaleimide, to assess the proportion of "alkaline" ribonuclease apparently bound to endogenous inhibitor. Total ribonuclease activity per ganglion was stimulated 1.3 fold by 1 day after injury and remained elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Biochemical experiments in the 1980s then revealed that uninjured sympathetic ganglia contain inactive ribonucleases [see references in (Bates et al, )] and that the total activity levels of alkaline ribonucleases increase in sympathetic ganglia after postganglionic nerve injury: this is the result of increased synthesis of ribonucleases as well as activation of existing ribonucleases. This activity becomes progressively restrained by one or more endogenous Ribonuclease Inhibitors (Bates et al, ). This is consistent with the idea that chromatolysis in sympathetic ganglia is due to ribonuclease activity and that any anabolic response occurs after progressive inhibition of cytoplasmic ribonucleases.…”
Section: Do Ribonucleases Cause Fragmentation Dispersal and Degranulmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical experiments in the 1980s then revealed that uninjured sympathetic ganglia contain inactive ribonucleases [see references in (Bates et al, )] and that the total activity levels of alkaline ribonucleases increase in sympathetic ganglia after postganglionic nerve injury: this is the result of increased synthesis of ribonucleases as well as activation of existing ribonucleases. This activity becomes progressively restrained by one or more endogenous Ribonuclease Inhibitors (Bates et al, ). This is consistent with the idea that chromatolysis in sympathetic ganglia is due to ribonuclease activity and that any anabolic response occurs after progressive inhibition of cytoplasmic ribonucleases.…”
Section: Do Ribonucleases Cause Fragmentation Dispersal and Degranulmentioning
confidence: 99%
“…It is not surprising, therefore, that exogenous treatment using various ribonucleases can degrade monoribosomes into “dust‐like” fragments in vitro (Steward, ; Rubel et al, ) [see also (Blasi et al, ; Gerashchenko and Gladyshev, )]. Interestingly, endogenous ribonucleases accompany ribosomes (Bransgrove and Cosquer, ; Bates et al, ; Bates et al, ; Schoenberg and Maquat, ) including in the adult mammalian brain (Datta and Ghosh, ) presumably constrained by an endogenous inhibitor (Allam et al, ). As will be seen next, particular ribonucleases are plausibly responsible for fragmentation of rough endoplasmic reticulum, dissociation of polyribosomes, degradation of monoribosomes and decay of RNA (Table ).…”
Section: Do Ribonucleases Cause Fragmentation Dispersal and Degranulmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the results obtained indicate a sharp decrease of free alkaline RNase activity of nervous tissue homogenates, persisting for 4 weeks after injury. On the contrary, the inhibitor-bound RNase activity [latent RNase activity, which is far higher than that of free alkaline RNase in the normal and pathological nervous tissues (Sajdel-Sulkowska and Marotta, 1984; Bates et al, 1985)], to which a key role on the regulatory mechanism of RNA turnover is attributed, was unmodified in both tissues at any time interval after crush. This indirectly suggests also that, in the regenerating neurons examined here, no changes in the content of the inhibitor factor were taking place.…”
Section: Discussionmentioning
confidence: 99%
“…A net growth of cellular processes (such as regenerating axonal tips) could be supported only by substantial increase of the protein synthesis rate and RNA content. We have also included the determination of alkaline RNase activities, because a possible relationship between the activities of RNases and phenomenon of growth has been demonstrated for many animal tissues (Rahman et al, 1969;Kraft and Shortman, 1970), including rat sympathetic ganglia, in which early increase of alkaline RNase activity up to 5 days after postganglionic nerve injury has been found (Bates et al, 1985).…”
Section: Changes Of Phospholipid-metabolizing and Lysosomal Enzymes Imentioning
confidence: 99%